Comparative study of outcome and complications of surgical management of benign gastric outlet obstruction - Prasad, Dinesh; Patel, Yash (International Surgery Journal, 2020)
Background: Gastric outlet obstruction (GOO) implies complete or incomplete obstruction of the distal stomach, pylorus, or proximal duodenum. There are many causes of benign GOO like acid ingestion, pyloric stenosis, peptic ulcer etc. The main aims of this study were to compare the perioperative morbidity and short and long term complications of different procedures for benign gastric outlet obstruction. Methods: This non-randomised retrospective study was undertaken in the department of General Surgery, SMIMER Hospital, Surat, Gujarat, India from August 2016 to July 2019. Thirty patients had been operated during this period and included in the study. Records of all 30 patients were retrieved and analysed. All these patients underwent pre-operatively upper GI scopy with biopsy and CECT abdomen. Results: Nausea and Vomiting was most common symptoms at time of presentation in our study. Incidence of wound infection in open Gastrojejunostomy group was very high i.e. 25% and hospital stay was also very high in open Gastrojejunostomy group. Post-operative PPI dependence was more common in Gastro-jejunostomy group in all follow up and there was no any requirement of PPI in Heineke-Mikukicz and Finney’s pyloroplasty group. Conclusions: On comparison of different surgical modalities for management of benign GOO, all surgeries performed laparoscopically were safe and carried comparatively less morbidities (perioperative, short term and long term) in comparison to open methods. Among all three laparoscopic procedures, outcome of laparoscopic pyloroplasty, both H-M pyloroplasty and Finney’s pyloroplasty were better than laparoscopic gastro-jejunostomy.